2022
DOI: 10.26434/chemrxiv-2022-04jdf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The origin of delayed polymorphism in molecular crystals under mechanochemical conditions

Abstract: Control over ball milling transformations is needed before the transformative potential of mechanochemical processing can be realized. Many parameters are known to affect the outcome of mechanochemical polymorphism, yet the energy of ball milling is itself often overlooked. We here demonstrate how milling energy can exert significant influence over the polymorphic outcome of ball mill grinding and be used to control the overall reaction profile. Milling energy exerts its effect on the reaction profile by chang… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…Atoms are coloured as: carbon (grey), oxygen (red) and nitrogen (blue). Please do not adjust margins Please do not adjust margins Following from our previous work, 13 we investigate here whether mechanochemically driven polymorphism can be controlled through changes in the equilibrium milling temperature. A 1:1 cocrystal of isonicotinamide (INA) and glutaric acid (GLU) was selected as a model system, Figure 1, which has one known polymorphic form (Form I) 27 that can be obtained by liquid assisted grinding (LAG).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atoms are coloured as: carbon (grey), oxygen (red) and nitrogen (blue). Please do not adjust margins Please do not adjust margins Following from our previous work, 13 we investigate here whether mechanochemically driven polymorphism can be controlled through changes in the equilibrium milling temperature. A 1:1 cocrystal of isonicotinamide (INA) and glutaric acid (GLU) was selected as a model system, Figure 1, which has one known polymorphic form (Form I) 27 that can be obtained by liquid assisted grinding (LAG).…”
Section: Resultsmentioning
confidence: 99%
“…For a polymorphic transformation to occur, a given crystal form must be driven over an energy barrier. This can be done for example by introducing defects into the crystal structure 13 or by increasing the equilibrium system temperature. To indirectly assess the effects of material activation (defect formation) on the polymorphism of INA:GLU, we explored neat grinding with one stainless steel ball (10 mm, 4.04 ± 0.02 g) at three milling frequencies (input energies), namely 50 Hz, 35 Hz, and 20 Hz (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 TRIS X-ray powder diffraction has been widely used to follow the formation and consumption of crystalline phases as a function of milling time, [4][5][6][7] and it has recently provided insights into the role of structural defects in activating mechanochemical transformations. 8,9 By using TRIS X-ray absorption spectroscopy 10 and optical fluorescence spectroscopy 11 changes in the electronic structure of matter can be followed during mechanochemical transformations. Additionally, vibrational [12][13][14][15][16] and NMR spectroscopies 17 provide insight into the evolution of molecular structure during milling.…”
Section: Introductionmentioning
confidence: 99%
“…By using TRIS thermometry, various authors have shown that over the course of a mechanochemical reaction, milling jars rarely exceed a few degrees. 9,19 Such findings have questioned the role of temperature as an underlying driving force in mechanochemical transformations.…”
Section: Introductionmentioning
confidence: 99%